Static in-line gas mixer for physiological capnogram simulation (Transactions on Additive Manufacturing Meets Medicine, 2024)
To physically simulate the physiological CO2 content over time (capnogram) in the exhaled air using a lung simulator, it is important to ensure adequate homogenization of the injected CO2 within the airflow. A static in-line mixing element is used for this purpose, which is required to fulfil various requirements at the same time: sufficient homogenization at different flow rates, small volume and low pressure drop. The focus of this study was the investigation of different Kenics mixer designs. Therefore, 13 Kenics mixers with different combinations of element length and number of elements are investigated for mixing performance and pressure loss using SolidWorks Flow Simulation. In addition to these Kenics designs, an SMX mixer with three parallel crossbars and six crossbars across the diameter is designed.For very low flow rates sufficient homogenization is not achieved with any mixer, but for most at higher flow rates. The homogenization is increased by reducing the size of the mixing elements and increasing the number of mixing elements in the mixer. Based on the results of the flow simulation of all 14 mixer designs, three mixers are selected that provide the best compromise between mixing performance and pressure drop are selected. To experimentally investigation of mixing performance, capnograms are simulated without any mixer at all and with each of the three printed mixers attached to the lung simulator. The selected mixers are the Kenics mixer with the smallest element length and four elements, the Kenics mixer with the second smallest element length and five elements and the SMX mixer. Analysis of the capnograms shows that homogenization without a mixer is inadequate, while each of the three mixers induces adequate homogenization. With the current CO2-sensor, there was no significant qualitative difference measurable in the mixing quality between the three selected mixers in the experimental test.
Keywords: capnogram; capnometry; lung simulation; flow simulation; gas mixing; kenics mixer; smx mixer; gas mixer; in-line mixer